2018
DOI: 10.1016/j.ijnurstu.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotional intelligence in health care professionals on caring behaviour towards patients in clinical and long-term care settings: Findings from an integrative review

Abstract: This review provides evidence that developing emotional intelligence in nurses may positively impact upon certain caring behaviours, and that there may be differences within groups that warrant further investigation. Understanding more about which aspects of emotional intelligence are most relevant for intervention is important, and directions for further large scale research have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 66 publications
9
103
0
17
Order By: Relevance
“…21 CSSD managers must be aware of how relationships affect the work environment, as motivation, leadership, empowerment and trust are inversely associated with levels of burnout. 22 Increasing the emotional intelligence of CSSD workers can improve the team's ability to deal with conflicts, motivate each other, 23 and be more careful in the workplace, 24 which can reduce role conflicts and stress.…”
Section: Discussionmentioning
confidence: 99%
“…21 CSSD managers must be aware of how relationships affect the work environment, as motivation, leadership, empowerment and trust are inversely associated with levels of burnout. 22 Increasing the emotional intelligence of CSSD workers can improve the team's ability to deal with conflicts, motivate each other, 23 and be more careful in the workplace, 24 which can reduce role conflicts and stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it improves their practical capacity, which benefits both patients and family members, as well as colleagues and co-workers [54]. This capacity to manage their emotions, remain calm, and experience empathy and distress allows these workers to think more clearly, which leads to better patient care [55]. Thus, emotional intelligence is a prominent variable in the nursing practice since it has the potential to affect the quality of care, patient outcomes, and the general well-being of the worker, as shown in the review by Raghubir [54].…”
Section: Introductionmentioning
confidence: 99%
“…Even though Maslen (2013) asserted that it is difficult to be compassionate, Paice, Heard and Moss (2002) reported that young doctors had a good relationship with patients as they exhibited compassion, openness and enthusiasm. This psychosocial support by clinicians has been reported to impact both patient satisfaction (Schoenfelder et al, 2011) and compliance (Petrilli et al, 2015;Nightingale, 2018) and should be a soft skill considered for all health care professions. However, practitioners must be sensitive to issues of personal space when trying to build rapport or show empathy, with a significant percentage of patients in this study reported feeling uncomfortable when the optometrist worked too closely to them.…”
Section: Discussionmentioning
confidence: 99%